Associação privada sem fins econômicos de assistência social: entre a lógica da filantropia e do reconhecimento da cidadania - o caso da Liga das Senhoras Católicas de São Paulo - Moussallem, Márcia (2008)
This dissertation proposes the introduction to a unique case study of the not-for-profit social assistance association Catholic Ladies League of Sao Paulo . The study stemmed initially from the interest in verifying the role of philanthropic associations that act in the field of social assistance, and that face new social matters in today's society. The fast-paced process of globalization that has been taking place since the twentieth century, and beginning of the twentieth-first century has brought forth significant changes in social, political and economic relations to all societies. In this new scenario one notices the emergence and relevance of notfor- profit associations in public spaces. In Brazil, most of these associations were born in the first moments of the colonization period, and were strongly influenced by the Catholic Church and by philanthropic practices. Thus the study has tried to verify if it is possible that a centennial association founded by the Catholic Church can make progress in its practices and actions towards paths which lead to citizen rights recognition. It is the general goal of this study to check the requisites for the association's actions that identify the passage from philanthropic actions to recognition of citizen rights. The methodology adopted was that of a unique case study by utilizing such research tools as: document analysis, direct observation, interviews with managers, technicians, partners and customers of the association, as well as professors that study the subject. As for the conclusion, it is observed that the association has been changing gradually throughout the different stages of the Brazilian history. After the country's redemocratization period, a new stage of the association with significant changes in the field of citizen rights is initiated. In the past nine years (1998 2007) it has been noticed the most relevant changes in all areas - from the administration to social programmes objectives conduct